Training operations reengineering survey : facilitator's guide - Shandler, Donald (Crisp Pub. Menlo ParkUS, 1997)
Presents a survey instrument designed to help trainers evaluate and re-engineer their organization's training function. 11 operational areas of the training function are identified and include: delivering technology-based training; designing learner-centered training; and developing teams.